2022
DOI: 10.32996/jmhs.2022.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Borderline Personality Disorder and Criminal Activity and Self-harm, Including Suicidal Behavior: A Systematic Review

Abstract: Borderline Personality Disorder (BPD) is an extraordinarily complex and least-understood mental disorder. It is currently known that BPD is related to aggression and anger. However, fewer studies focused on the prevalence of BPD symptoms among criminal offenders and their association with crime. This systematic review act per Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 guidelines. We searched PubMed, PubMed Central (PMC), Medical Literature Analysis and Retrieval System Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This is interesting, as there has not been much research surrounding criminality and the underlying impulsivity factor related to ADHD, BED, and BPD. Few studies have investigated the association between BPD symptoms and criminality, even though it has been linked to violence and aggressiveness [ 32 ]. Therefore, this study finding suggests that investigating impulsivity and its interactions in ADHD with comorbid BPD and BED may help elucidate predictable patient behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting, as there has not been much research surrounding criminality and the underlying impulsivity factor related to ADHD, BED, and BPD. Few studies have investigated the association between BPD symptoms and criminality, even though it has been linked to violence and aggressiveness [ 32 ]. Therefore, this study finding suggests that investigating impulsivity and its interactions in ADHD with comorbid BPD and BED may help elucidate predictable patient behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological and criminological researchers have continuously sought to comprehend countless interacting biological, psychological, and social factors to clarify why some people tend to involve in criminal and antisocial behaviors ( 1 ). Numerous theories attribute the basis of these behaviors to factors such as personality ( 2 ), mental disorders ( 3 ), ineffective parenting ( 4 ), cognitive factors and skills ( 5 ). Also, numerous studies have revealed that men are more prone to criminal and anti-social behaviors compared to women ( 6 , 7 ).…”
mentioning
confidence: 99%